Heel Raise Exercise: Effects on ABI and Peripheral Neuropathy - Andani, Kadek Novi; Nisman, Wenny Artanty; Pangastuti, Heny Suseani (Universitas Muhammadiyah Surakarta, 2026)
Vascular complications, particularly impaired peripheral perfusion as reflected by reduced Ankle Brachial Index (ABI) values and the occurrence of peripheral neuropathy, are frequently observed in individuals with type 2 diabetes mellitus (T2DM). These conditions significantly contribute to an increased risk of diabetic foot ulceration and lower limb amputation. Therapeutic exercise targeting the lower extremities represents a non-pharmacological preventive strategy, among which Heel Raise Exercise (HRE) is considered practical and feasible for routine implementation. This study aimed to evaluate the effect of HRE on ABI values and peripheral neuropathy scores in patients with T2DM. This study employed a quasi-experimental design with a nonequivalent control group approach. A total of 62 participants were recruited using purposive sampling from the service area of Buleleng I Primary Health Care Center. Group allocation into intervention and control groups was conducted through non-random assignment based on participant enrollment order and operational considerations at the study site. ABI measurements were performed using an 8 MHz Doppler ultrasound device in conjunction with a sphygmomanometer, while peripheral neuropathy was assessed using the Michigan Neuropathy Screening Instrument (MNSI). Statistical analysis involved paired t-tests to examine within-group differences before and after the intervention and independent t-tests to compare mean differences between groups. The results demonstrated that the intervention group exhibited an increase in mean post-intervention ABI values to 0.93, accompanied by a reduction in peripheral neuropathy scores to 2.89. In contrast, no statistically significant changes were identified in the control group. The mean differences in ABI (0.07 ± 0.04) and peripheral neuropathy scores (0.40 ± 0.61) in the intervention group were statistically significant. In conclusion, Heel Raise Exercise was shown to be effective in improving peripheral vascular status and reducing peripheral neuropathy severity in patients with type 2 diabetes mellitus.